Theoretical perspectives on digital globalization: A critical review - Ibrahim, Isa Ali; Baballe, Muhammad Ahmad (Edelweiss Applied Science and Technology, 2024)
The Fourth Industrial Revolution (4IR), or Industry 4.0, is transforming the world through rapid technological advancements, integrating cutting-edge digital technologies into daily life. This revolution builds upon previous industrial stages, driving significant engineering, business, manufacturing, and technological innovations. While Industry 4.0 offers numerous benefits, including enhanced efficiency, economic growth, improved quality of life, informed decision-making, and sustainability, it also poses substantial challenges. These include exacerbating inequality, job displacement by artificial intelligence, increased cybercrime, privacy concerns, and technological dependency. This study examines the dualities of Industry 4.0, emphasizing the need for balance to ensure technological progress serves humanity. The research advocates for harnessing technological advancements to promote equitable economic growth, social well-being, and human flourishing.